Pelatihan Optimalisasi Konten Instagram dengan Menggunakan Aplikasi ChatGPT - Muhardono, Ari; Citradika, Didha Putri; Satrio, Danang; Adriyana, Rika; Khasanah, Kharismatul (LPPM Universitas Pekalongan, 2024)
Silvia Honey is an individual business unit in the livestock sector in Pekalongan City. Silvia Honey was pioneered at the beginning of 2018 or approximately 5 years running. In its development, this honeycomb business unit has experienced quite rapid development but its reach is still limited to local and only relies on word of mouth marketing. The use of digital marketing to reach a larger market potential is still not optimal. Based on an interview with business owner Rizki Silva Pinusa, he still only uses Instagram in his marketing. The obstacle experienced is not yet mastering how to create interesting Instagram content so that it can influence purchasing decisions. The aim of this community service activity is to provide training on optimizing Instagram social media and using ChatGPT to support the marketing of Silvia Honey so that it can create interesting and relevant content on Instagram social media. The result of this activity was an increase in participants' knowledge and skills by 32.33%.